Taiping heritage town: british colonial legacy landscape master plan - Ahmad, Hamidah; Mohd. Zain, Zainul Hakim; Yaacob, Rozinah (Faculty Built oF Environment, 2010)
British colonization period in the 19th century made tarping the first tin mining and capital town of Malaysia, previously known as British Malaya. Taiping's possession of a wealth of historical buildings, structures and sites provide tangible evidence of the unique and intricate history and culture formed over the past centuries. Today, Taiping's British Colonial legacy not only form the town's urban historic landscape but also relents a 'sense of place' to the town. Taiping local Authority wanted to ensure that this heritage can be continously enjoyed, sustained and maintained by commissioning Taiping's Heritage study, encompassing both its natural and cultural heritage. The purpose of the study was to formulate and propose Taiping's Heritage Town Landscape Master Plan. The Master Plan is to become a multifaceted conservation strategy to address the major conservation issues. It is to be a policy document intented to guide and coordinate conservation activity in Taiping. Conserving the taiping of the past as a part of the Taiping of the future will be a vital component of the town's development in the years to come. The conservation and enhancement of taiping's heritage resources can and will continue to significantly contribute to the town's economic revitalization, cultural and tourism opportunities, image, and quality of life. A comprehensive inventory, overlays, assessment and planning of Taiping's heritage resources was carried out as part of the processes in preparing the Master Plan. the potentials, constraints and threats existing in the town's urban landscape were identified and analysed. this paper discusses the processes of the study and its outcome, a document to guide and coordinate Taiping's heritage landscape activity and establish a framework for decision making. It outline procedures for heritage identification and interpretation, guides the stewardship of public owned heritage resources, and identificies specific improvements to the existing regulatory framework.